Infrastructure, FDI and manufacturing exports in Africa: the firm level analysis - Moyo, Busani (My University, 2015)
The primary aIm of this study is to investigate the role that is played by the quality of infrastructure on export participation and on foreign direct investment using firm level data from the World Bank and employing maximum likelihood techniques such as the Tobit and Probit models. Results show that firm size, foreign ownership, internet access, international distance, electricity, customs and generator ownership matter in influencing export participation. Thus the reason why very few firms in Africa are outward oriented is partly because of poor market access and poor electricity and customs infrastructure. Ln the case of foreign direct investment (FDI) results show that foreign firms are attracted to a market, bigger in size and that market access is also very important. FDI results also show that a big market in an environment characterized by acute power problems negatively affects market seeking FDI. Customs problems generally have a weak negative effect on the probability to be foreign invested particularly inward FDI, but days to export matter to outward looking foreign producers. Water problems do not seem to matter for both FDI firms and exporters in this study. In light of these findings, there is need therefore for the government in collaboration with multilateral institutions like the World Bank, United Nations and other donor agencies to mobilise resources to improve Africa's infrastructure facilities particularly customs, power and international transport facilities . This could also be done by involving the private sector through various Public Private Partnership arrangements.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic & Business Sciences, 2011.
Keywords: Investments, Foreign--Africa; International business enterprises--Africa; Africa--Economic conditions